THE TRAINING NEEDS OF DUSIT THANI COLLEGE’s SENIOR STUDENTS - Praweena Kasai ประวีณา คาไซ (Dusit Thani College Journal, 2018)
This research aimed to study the training needs for career preparation of Dusit Thani College’s senior students both generic and specific training as classified by their fields of interest and the preferred training style, place and the length of time of the training program. This study was a survey research. A sample group was senior students of Dusit Thani College. Descriptive statistics was applied to calculate for frequency and percentage to analyze personal data of the respondents, training program, and desired training style. The total numbers of students responding to the survey were 209 respondents; of which, 103 were male students and 106 were female students. The most desired business field that Dusit Thani College’s students would like to join was being a business owner, from 70 respondents or 33.49 percent of total respondents, followed by working in Hotel Resort & Spa business, from 64 respondents or 30.62 percent. The students showed their preference for the following training programs from the following categories: training programs that most corresponded to students’ interest in English and ASEAN languages were Basic English Conversation course, from 137 respondents or 65.55 percent, followed by English for Job Application and Job Interview course, from 122 respondents or 58.37 percent. Training programs that most corresponded to students’ interest in computer skills were Video Clipping Program course such as Adobe Premiere, Sony Vegas, Windows Movie Maker, from 114 respondents or 54.55 percent, followed by Social Network and Social Media for Career course, from 91 respondents or 43.54 percent. Training programs that most corresponded to students’ interest in job application were Personality Development for Professionals course, from 133 respondents or 63.64 percent, followed by Preparation Techniques for Job Interview course, from 107 respondents or 51.20 percent. Training programs that most corresponded to students’ interest in conducting a business and working abroad were Preparation for Working Abroad course, from 144 respondents or 68.90 percent, followed by Small and Medium Enterprise Establishment course, from 84 respondents or 40.19 percent. Training programs that most corresponded to students’ interest in thinking process were Creative Thinking course, from 145 respondents or 69.38 percent, followed by Critical Thinking course, from 77 respondents or 36.84 percent. Moreover, the preferred training style was classroom-based training over one day period during the special session, on weekdays only. The preferred training room was theater room at Dusit Thani College. The researcher recommended a further study on this topic in comparison with other institution in order to analyze what the supplement training course is needed.